Índices de massa muscular e suas relações com função muscular, perfil metabólico e densidade mineral óssea em mulheres obesas - Carvalho, Nara Nóbrega Crispim (2019)
This study aimed to evaluated the frequency of sarcopenia in obese women with recommendation for bariatric surgery (BS) through three muscle mass indexes (MMIs). In addition, it was compared sarcopenic obese (SO) women with non-sarcopenic obese (NSO) women regarding their age, anthropometric measurements, blood pressure, body composition, handgrip strength (HS), six-minute walk test (6MWT), metabolic profile and bone mineral density (BMD). Finally, it was investigated any correlation between the MMIs and the studied variables and the correlation between them. This was a cross-sectional study with 62 obese women (18-60 years old), belonging to the outpatient clinic of Lauro Wanderley University Hospital and private clinics, João Pessoa, Brazil, conducted between March and September 2018. They were allocated in two groups; SO and NSO for each MMI evaluated. Sarcopenia was defined by three different MMIs: a) Appendicular skeletal muscle mass (ASM) adjusted for weight (wt): ASM/wt x 100,%, b) ASM adjusted for body mass index (BMI): ASM/BMI, m2 and c) ASM adjusted for squared height (ht2): ASM/ht2, kg/m2. We considered SO women those who were in the lowest quintile for each MMI and those who were in the other quintiles, as NSO. Body composition was evaluated by bioimpedance (inbody-370), BMD by dual-energy X ray absorpptiometry (Lunar Model 8743, Medical Systems Lunar, Madison, USA), HS by Jamar dynamometer and physical function by 6MWT. In addition, we assessed fasting glycemia, glycated hemoglobin, homeostatic model assessment-insulin resistance (HOMA-IR), plasma insulin, total cholesterol, low density lipoprotein (LDL), high density lipoprotein (HDL), triglycerides and high sensitivity quantitative C-reactive protein. Participants presented mean age: 39.53 ± 8.99 years, wt: 108.6 ± 13.86 kg and BMI: 42.6 ± 4.64 kg/m2. Sarcopenic obesity was found in 30.5% by ASM/wt x 100, 20.33% by ASM/BMI and 20.33% by ASM/ht2. SO women by ASM/wt x 100 showed higher body fat percentage (BFP), lower FPM and lower BMD in L1-L4, in the femoral neck (FN) and in total femur (TF) than NSO group (p<0.05). For ASM/BMI, OS group had a higher BMI, higher BFP, lower HS and 6MWT distance than NSO (p<0.05). SO women identified by ASM/ht2 had lower weight, BMI, diastolic blood pressure and BMD in FN and TF (p<0.05). Regarding the association of the MMIs with the variables analyzed; ASM/wt x 100 was negatively associated with BMI, BFP and fat mass of upper limbs, and positively correlated with HS and BMD of all sites (p<0.05). ASM/BMI was negatively associated with BMI and BFP and was positively correlated with BMD in L1-L4 and FN (p<0.05). ASM/ht2 was positively associated with wt, BMI, appendicular fat mass, HS, HOMA-IR and BMD in TF (p<0.05). ASM/wt x 100 had an excellent positive correlation with ASM/BMI (p <0.05). It was concluded that the frequency of sarcopenic obesity in women with recommendation for CB was higher when using ASM/wt x 100 than the other indices. SO women by ASM/wt x 100 and ASM/BMI had higher adiposity and lower FPM. The ASM/BMI was the only one to identify a low 6MWT, whereas only the ASM/wt x 100 identified a low BMD at all evaluated sites.